Japanese Continuous Improvement Practices Implementation in Vietnamese Manufacturing Companies - Phan, Chi Anh (Đại học Kinh tế, 2016)
This study investigates the implementation of Kaizen practices in Vietnamese manufacturing companies. Statistical techniques such as ANOVA and regression are applied to analyze the data are collected from 64 Vietnamese manufacturing companies through a questionnaire survey during 2011-2012. The results of statistical analysis indicate that Japanese continuous improvement practices have positive relationship with companies' performance on quality, cost, and delivery. We conclude that Vietnamese companies should further emphasis on implementing Japanese management practices to enhance the performance.